The Association Between Arterial Carbon Dioxide Tension and Outcomes After Cardiac Arrest: A Systematic Review and Meta-analysis - Mckenzie, N.F.; Williams, Teresa; Tohira, Hideo; Ho, K.M.; Finn, Judith (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Introduction: Arterial carbon dioxide (PaCO2) elimination is impaired during cardiac arrest (CA) due to inadequate perfusion of the lungs. Both high and low PaCO2 after return of spontaneous circulation from CA are common due to accumulation of CO2 during CA and excessive mechanical ventilation respectively. Maintaining a normal PaCO2 is recommended as a therapeutic target after CA. Whether this recommendation is fully supported by existing evidence remains uncertain, and is assessed in this systematic review and meta-analysis. Methods: MEDLINE, EMBASE, CINAHL and Cochrane CENTRAL were searched for studies that evaluated the association between PaCO2 and outcomes after CA. The primary outcome was hospital survival. Secondary outcomes included neurological status at the end of each study’s follow up period. Meta-analysis was conducted if statistical heterogeneity was low. Results: Nine observational studies were included in this systematic review; eight had sufficient quantitative data for meta-analysis. Defining hypo- and hypercarbia with PaCO2 cut-points of <35 and >45 mmHg, normocarbia was associated with increased hospital survival (odds ratio [OR] 1.30, 95% confidence interval [CI] 1.23, 1.38). Normocarbia was also associated with a good neurological outcome (cerebral performance category score 1 or 2) compared to hypercarbia (OR 1.69, 95% CI 1.13, 2.51). This analysis included an additional study with a slightly different definition for normocarbia (PaCO2 30 to 50mmHg). Exclusion of this study resulted in loss of statistical significance (OR 1.42, 95% CI 0.89, 2.28). Conclusions: From the limited data available normocarbia after CA is associated with better hospital survival and neurological outcome compared to either hypo- or hypercarbia. This is consistent with current post-resuscitation guidelines’ recommendations. These findings should be confirmed by adequately powered clinical trials.